An assessment of prognostic immunity markers in breast cancer. (December 2018) - Yang, Benlong; Chou, Jeff; Tao, Yaozhong; Wu, Dengbin; Wu, Xinhong; Li, Xueqing; Li, Yan; Chu, Yiwei; Tang, Feng; Shi, Yanxia; Ma, Linlin; Zhou, Tong; et al.
Abstract Tumor-infiltrating lymphocytes (TIL) and immunity gene signatures have been reported to be significantly prognostic in breast cancer but have not yet been applied for calculation of risk of recurrence in clinical assays. A compact set of 17 immunity genes was derived herein from an Affymetrix-derived gene expression dataset including 1951 patients (AFFY1951). The 17 immunity genes demonstrated significant prognostic stratification of estrogen receptor (ER)-negative breast cancer patients with high proliferation gene expression. Further analysis of blood and breast cancer single-cell RNA-seq datasets revealed that the 17 immunity genes were derived from TIL that were inactive in the blood and became active in tumor tissue. Expression of the 17 immunity genes was significantly (p < 2.2E-16, n = 91) correlated with TILs percentage on H&E in triple negative breast cancer. To demonstrate the impact of tumor immunity genes on prognosis, we built a Cox model to incorporate breast cancer subtypes, proliferation score and immunity score (72 gene panel) with significant prediction of outcomes (p < 0.0001, n = 1951). The 72 gene panel and its risk evaluation model were validated in two other published gene expression datasets including Illumina beads array data METABRIC (p < 0.0001, n = 1997) and whole transcriptomic mRNA-seq data TCGA (p = 0.00019, n = 996) and in our own targeted RNA-seq data TARGETSEQ (p < 0.0001, n = 303). Further examination of the 72 gene panel in single cell RNA-seq of tumors demonstrated tumor heterogeneity with more than two subtypes observed in each tumor. In conclusion, immunity gene expression was an important parameter for prognosis and should be incorporated into current multi-gene assays to improve assessment of risk of distant metastasis in breast cancer. Genomic testing: Tumor-infiltrating immune cells express detectable gene signature The elevated expression of 17 immunity-related genes is associated with better outcomes among women with aggressive forms of estrogen receptor–negative breast cancer. Zhiyuan Hu from the University of North Carolina at Chapel Hill, USA, and colleagues identified the 17-gene set by analyzing a larger expression dataset from close to 2, 000 patients. Single-cell sequencing revealed that the genes were turned on in a group of cancer-fighting immune cells known as tumor-infiltrating lymphocytes, but were inactive in circulating blood cells. The researchers incorporated the immunity-related genes into a larger panel of genes involved in proliferation, invasion and other relevant biological processes. The resulting 72-gene test was an accurate predictor of the risk for developing distant metastases. The findings suggest that immunity-related genes should be incorporated into current multi-gene prognostic assays for women with breast cancer.